KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MOTIVASI GURU - MUH. Jafar B. (Makassar Journal of Social Sciences, 2023)
Abstract ; This study aimed to determine the principal's leadership in increasing the motivation of teachers at SMPN 1 Pa'jukukang Bantaeng population in this study were the teachers SMPN1 Pa'jukukang Bantaeng number of 31 teachers. In this study sample was not withdrawn because the researchers were able to reach this population. Held data collection techniques for observation, interview and observation serata documentation. The results showed that; School leadership in SMPN1 Pa'jukukang Bantaeng quite good, work motivation of teachers in SMPN 1 Pa'jukukang Bantaeng quite good so that it can be concluded with a good school leadership can increase the motivation of teachers SMPN1 Pa'jukukang Bantaeng